Otevřená inovace - přístup překračující známé hranice - Muška, Milan; Králík, Jiří (Univerzita Pardubice, 2009)
Most innovations fail, and companies, that don´t innovate, die. Open Innovation is new approach of what to do with ideas or problems, it exploits possibilities of the open system. That assumes that firms can and should use external ideas as well as internal ideas, external solutions as well as internal solutions, and internal and external paths to market, as the firms look to advance their technology or realize potential value of ideas or problem solutions.
Keywords: Innovation; open innovation; closed innovation; user innovation; cumulative innovation; business models; open systems